Association of Dual Antiplatelet Therapy and Hemoglobin Level in Cardiovascular Patients-A Single Centered Comparative Observational Study - Gobu; Emmanuel; Singh, Daniel Sundar; Elumalai, Prakashraj; Ayas, Roshan Nawaz; Subburaj, Solai Ganesh (International Journal of Pharmaceutical Investigation, 2025)
Background Cardiovascular diseases are increasingly becoming a major cause of morbidity and mortality around the world. About half of the deaths due to non-communicable diseases are attributed to some form of cardiovascular disease. Pharmaceutical and surgical interventions are often employed to treat these diseases. In this study, the effects of DAPT on hemoglobin of the patients who have undergone coronary intervention are studied. Materials and Methods A Comparative observational study was conducted for a period of six months in a quaternary care hospital. On the basis of Convenience Sampling Technique, the sample size was 169. Patient of age group above 18 years taking Dual Antiplatelet Therapy with no hematological comorbidities were included. A follow-up schedule was established for each participant, outlining specific time period for monitoring hemoglobin levels for duration of about 6 months and monitored changes in hemoglobin level in patients taking antiplatelet medication. Results and Discussion The study revealed that both DAPT regimens led to a significant reduction in hemoglobin levels over the course of six months. Specifically, the Ticagrelor+Aspirin combination (Group A) was associated with increased hemoglobin reduction than Clopidogrel+Aspirin combination (Group B). Conclusion The patients taking ticagrelor+aspirin combination observed to decreased hemoglobin levels than the patients taking clopidogrel+aspirin combination. This comparative study will shed clear insight on the association of dual antiplatelet therapy and hemoglobin levels in cardiovascular patients.
Keywords: Cardiovascular diseases; CAD; DAPT; Hemoglobin